La mierda y el amor - Silva Téllez, Armando (Taller de Edición Rocca, 2017)
Julio Almanza, 50, falls in love with Anís Strauss, 35. Both travel to different places in Istanbul (Asia), Goa (India), and Bangkok (Thailand). All goes well until Anis becomes fully involved with religion, while Julio slowly loses track of his sexuality.